Le vécu de l’hépatite C chez des femmes migrantes vivant en Île-de-France - Antunes Maia, Marta (2012)
The living of hepatitis C among migrant women in Ile-de-France We interviewed four migrant women, from different cultural origins and infected with hepatitis C virus, in order to analyze the influence of social context and migratory course on the disease’s management. The condition of being a woman and the migrant’s statute can constitute factors worsening the living of the disease, because the degree of vulnerability and precariousness associated to being women and migrants is more important than within the population in general. The existence or absence of stigmatization and rejection, of support of the entourage and of access to health care are fundamental elements in living of hepatitis C disease and its treatment. The individuals from underprivileged classes are more vulnerable in facing the disease and they also are those whose propensity to take care of themselves is lower. In general, the immigrants are included in these groups of individuals.